Unveiling crystallization mechanism for controlling nanocrystalline structure in glasses. Issue 5 (May 2020) - Ye, Qilin; Weng, Kaibo; Guan, Shangsheng; Lin, Changgui
Abstract: Controlling nanocrystalline structure in glasses renders the exploration of new composite multiphase (glass-ceramic) materials with novel functionalities that determined by the precipitated nanocrystals and residual glassy matrix. Previous microstructural investigation of glass-ceramics focused only on one aspect of nanocrystalline structures, e.g., nano-polycrystalline or single nanocrystalline. The recognition of the microscopic mechanism of nanostructure formation in glasses is absent. Here, we use advanced microscopic techniques to show the formation of different nanocrystalline structures composed of nano-polycrystals and single nanocrystals in 80GeS2 ·20In2 S3 and 72.5GeS2 ·14.5Sb2 S3 ·13RbCl glasses, respectively. Crystallization mechanism for controlling the nanocrystalline structure in glasses was revealed to depend on whether the glass network former participates in crystallization process. The results may shed light not only on glass crystallization mechanism, but also on the fundamental nature of the network structure of chalcogenide glasses.